How Effective Are Hiring Subsidies to Reduce Long-Term Unemployment among Prime-Aged Jobseekers? Evidence from Belgium - Sam Desiere; Bart Cockx (Institute of Labor Economics (IZA), 2021)
Hiring subsidies are widely used to create (stable) employment for the long-term unemployed. This paper exploits the abolition of a hiring subsidy targeted at long-term unemployed jobseekers over 45 years of age in Belgium to evaluate its effectiveness in the short and medium run. Based on a triple difference methodology the hiring subsidy is shown to increase the job finding rate by 13% without any evidence of spill-over effects. This effect is driven by a positive effect on individuals with at least a bachelor's degree. However, the hiring subsidy mainly created temporary short-lived employment: eligible jobseekers were not more likely to find employment that lasted at least twelve consecutive months than ineligible jobseekers.
Keywords: H22; J08; J18; J23; J38; J64; J65; J68; 330; hiring subsidies; long-term unemployment; prime-aged jobseekers; triple difference; temporary help agencies